Age-Dependent Loss of Mitochondrial Function in Epithelial Tissue Can Be Reversed by Coenzyme Q10 - Daniel Schniertshauer; Daniel Gebhard; Jörg Bergemann (Journal of Aging Research)
The process of aging is characterized by the increase of age-associated disorders as well as severe diseases. Due to their role in the oxidative phosphorylation and thus the production of ATP which is crucial for many cellular processes, one reason for this could be found in the mitochondria. The accumulation of reactive oxygen species damaged mitochondrial DNA and proteins can induce mitochondrial dysfunction within the electron transport chain. According to the “mitochondrial theory of aging,” understanding the impact of harmful external influences on mitochondrial function is therefore essential for a better view on aging in general, but the measurement of mitochondrial respiration in skin cells from cell cultures cannot completely reflect the real situation in skin. Here, we describe a new method to measure the mitochondrial respiratory parameters in epithelial tissue derived from human skin biopsies using a XF24 extracellular flux analyzer to evaluate the effect of coenzyme Q10. We observed a decrease in mitochondrial respiration and ATP production with donor age corresponding to the “mitochondrial theory of aging.” For the first time ex vivo in human epidermis, we could show also a regeneration of mitochondrial respiratory parameters if the reduced form of coenzyme Q10, ubiquinol, was administered. In conclusion, an age-related decrease in mitochondrial respiration and ATP production was confirmed. Likewise, an increase in the respiratory parameters by the addition of coenzyme Q10 could also be shown. The fact that there is a significant effect of administered coenzyme Q10 on the respiratory parameters leads to the assumption that this is mainly caused by an increase in the electron transport chain. This method offers the possibility of testing age-dependent effects of various substances and their influence on the mitochondrial respiration parameters in human epithelial tissue.